GAMBARAN MEKANISME KOPING IBU YANG MEMILIKI ANAK BERKEBUTUHAN KHUSUS DI SLB NEGERI 2 INDRAMAYU - Dedeh Husnaniyah; Kamsari Kamsari; Nia Nursoleha (Jurnal Vokasi Keperawatan (JVK), 2020)
Coping mechanisms are the means by which individuals solve problems and changes. Parents who have ABK (children with special needs) result in the emerge new changes in the family and cause different coping mechanisms of each mother. This research is to know how to describe the coping mechanism of mother who have children with special needs in SLB Negeri 2 Indramayu.The research design used is quantitative research with descriptive approach. The population of mothers who have children in SLB Negeri 2 Indramayu. The data analysis using univariate. The population is 91 respondents.The results showed that in general the mechanism of coping mother includes 52.4% of respondents who have adaptive coping mechanism. Mother coping mechanism based on final adult category 61,0% of respondents have adaptive coping mechanism. Mechanism of coping mother based on education with high school education category 54,1% of respondents have adaptive coping mechanism. Mechanism of coping mother based on occupation category of housewife 52,4% of respondents have adaptive coping mechanism.Conclusion of research entitled Description of Mechanism of Mother Coping Who Have Children with Special Needs In SLB Negeri 2 Indramayu is adaptive coping mechanism.